Design and Analysis of a New High Step-Up Converter Using Switched-Inductor-Capacitor Voltage Multiplier Cells for Photovoltaic Application - Ramachandran Rajesh; Natarajan Prabaharan; Eklas Hossain (IEEE Journal of the Electron Devices Society)
This article proposes a new high-gain converter to attain higher output voltage without coupled inductors. The operation of the proposed converter is examined under continuous conduction mode (CCM) and discontinuous conduction mode (DCM). Also, the mathematical expressions for the design of inductors, capacitors, voltage and current stress of semiconductor devices are provided. The proposed converter is simulated in MATLAB-Simulink and validated the effectiveness of the performance using a laboratory-based Prototype of 250 W at 50 kHz with a 60% duty cycle. The experimental results of the individual components are matched with the simulated results. Due to the continuous input current, the proposed converter is suitable for photovoltaic (PV) applications.